Synergistic therapeutic effect of low-dose bevacizumab with cisplatin-based chemotherapy for advanced or recurrent cervical cancer. Issue 12 (6th October 2021) - Liu, Chia-Hao; Kung, Yen-Hsuan; Chien-Fu Lin, Jeff; Chuang, Chi-Mu; Wu, Hua-Hsi; Jiang, Ling-Yu; Shih, Ying-Chu; Wang, Peng-Hui; Chen, Yi-Jen
Abstract : Background: Cisplatin-based chemotherapy (CBC) is highly efficacious for advanced cervical cancer; its efficacy can be enhanced by combining with 15 mg/kg (standard dose) bevacizumab (BEV). However, this standard dose is associated with various adverse events (AEs). Therefore, in this retrospective study, we analyzed the survival outcomes and AEs in patients with advanced or recurrent cervical cancer treated with CBC in combination with BEV 7.5 mg/kg. Methods: Registered patient data were retrieved between October 2014 and September 2019, and 64 patients with advanced or recurrent cervical cancer treated with CBC + BEV (n = 21) or CBC alone (n = 43) were analyzed. The primary endpoints were progression-free survival (PFS) and overall survival (OS); the secondary endpoints were the frequency and severity of AEs. The Cox proportional-hazards model was applied to explore prognostic factors associated with PFS and OS. Results: The 1-, 2-, and 3-year PFS rates (95% CI) were 36.24% (22.0-50.5), 20.7% (9.8-34.2), and 17.7% (7.7-31.1) for the CBC group; and 71.4% (47.1-86.0), 51.0% (27.9-70.1), and 51.0% (27.9-70.1) for the CBC + BEV group, respectively. The 1-, 2-, and 3-year OS rates were 62.6% (46.4-75.18), 32.4% (18.8-46.9), and 23.2% (11.2-37.6) for the CBC group; and 85.7% (61.9-95.1), 66.6% (42.5-82.5), and 55.5% (27.1-76.7) for the CBC + BEV group, respectively. The CBC + BEV group presented higher PFS and OS rates, p = 0.003 and p = 0.005, respectively. Proteinuria (6 vs 9, p = 0.025) and hypertension (0 vs 10, p < 0.001) were less common, but anemia was more common in the CBC group (35 vs 11, p = 0.021). Conclusion: Overall, CBC + BEV significantly improved the PFS and OS compared with CBC alone. CBC + BEV also prevents severe AEs and hence is an efficacious and safe therapeutic option.